Preparation of highly porous activated carbons from peanut shells as low-cost electrode materials for supercapacitors. (February 2021) - Zhan, Yinbo; Zhou, Huiming; Guo, Feiqiang; Tian, Beile; Du, Shilin; Dong, Yichen; Qian, Lin
Highlights: Three-dimensional porous carbons were synthesized from peanut shells. The highest specific surface area of 2936.8 m 2 g −1 was achieved via KOH activation. The capacitance of KOH-AC reached 440 F g −1 at 0.1 A g −1 . The specific power reached 2495.5 W kg −1 at an specific energy of 39.1 W h kg −1 . Abstract: The synthesis of three-dimensional porous biomass carbons from the abundant peanut shells is investigated employing K2 CO3, KCl, KOH, and NaOH as the activators for the application as low-cost electrode materials for supercapacitors. The results show that KCl-AC and K2 CO3 -AC are mainly composed of microporous structures, while KOH-AC and NaOH-AC show a well-developed porous structure consisting of both micropores and mesopores, and NaOH activation is more inclined to form mesopores than KOH. KOH-AC achieves the highest specific surface area of 2936.8 m 2 g −1 and a relatively higher graphitization degree among these samples. At 1 A g −1, the gravimetric specific capacitances of K2 CO3 -AC, KCl-AC, NaOH-AC and KOH-AC are 250, 210, 284, and 339 F g −1 in the three-electrode system. The gravimetric specific capacitance of KOH-AC reaches 440 F g −1 at 0.1 A g −1 and retains 286 F g −1 at 10 A g −1 . In a two-electrode system, KOH-AC exhibits a high specific energy of 39.1 W h kg −1 at a specific power of 2495.5 W kg −1 . KOH-AC also shows low internal resistance and good charge and discharge performance, and high cycle stability of 80% capacitance retention is achieved for 10000 cycles at 5 A g −1 . Graphical abstract: Image, graphical abstract